Bridging abstract to concrete: The SPLDV board as an innovative tool for teaching systems of linear equations - Chatra Arlinta Maurilla; Puguh Darmawan (Polyhedron International Journal in Mathematics Education, 2025)
This qualitative case study examines the effectiveness of the SPLDV Board, a color-coded manipulative tool, in teaching systems of linear equations with two variables to 37 mathematics education students. Through inquiry-based instruction and systematic questioning, the study analyzed students' conceptual understanding, procedural fluency, and engagement patterns. Results demonstrated that the SPLDV Board's visual scaffolding significantly improved students' ability to identify coefficients, execute cross-multiplication procedures, and understand underlying mathematical structures, with all participants achieving fluent responses to guiding questions. However, limitations emerged: the tool only works for systems with unique solutions and some students remained passive during instruction. Findings provide practical guidance for developing accessible manipulative materials that support both procedural and conceptual learning in algebra, with design principles transferable to other mathematical topics requiring multi-step problem-solving.